An introduction to multivariate statistical analysis - Anderson, T. W. (New York : Wiley, 1958)
For more than four decades An Introduction to Multivariate Statistical Analysis has been an invaluable text for students and a resource for professionals wishing to acquire a basic knowledge of multivariate statistical analysis. Since the previous edition, the field has grown significantly. This updated and improved Third Edition familiarizes readers with these new advances, elucidating several aspects that are particularly relevant to methodology and comprehension.
Includes index.
Includes bibliographical references: p. 352-368.
aia 07/06/2018
Keywords: Multivariate analysis